2014
DOI: 10.1007/s00005-014-0312-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Kynurenic Acid Concentration in Patients Undergoing Cardiac Surgery: Effect of Anaesthesia

Abstract: Increases in plasma kynurenic acid (KYNA) concentration relate to the severity of inflammation. The aim of this study was to analyse changes in plasma KYNA concentration and neutrophil/lymphocyte ratio (NLR) in cardiac surgery patients. Additionally, the effect of anaesthesia was analysed. Adult cardiac surgery patients under intravenous general anaesthesia were studied. Additionally, some patients received sevoflurane (SEV) prior to cardiopulmonary bypass. Plasma KYNA concentration and NLR were measured befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
(109 reference statements)
1
4
0
Order By: Relevance
“…The effect of surgery on plasma KYNA concentration has been poorly documented, but it can be assumed that a significant increase in plasma proinflammatory cytokines following the surgical procedures implemented may increase the activity of IDO and enhance production of kynurenine metabolites. This hypothesis is in accordance with our previous study, which demonstrated a significant increase in plasma KYNA concentration following cardiac surgery [ 30 ]. Likewise, Forrest et al presented an increase in plasma KYNA concentration after major surgery [ 31 ].…”
Section: Discussionsupporting
confidence: 94%
“…The effect of surgery on plasma KYNA concentration has been poorly documented, but it can be assumed that a significant increase in plasma proinflammatory cytokines following the surgical procedures implemented may increase the activity of IDO and enhance production of kynurenine metabolites. This hypothesis is in accordance with our previous study, which demonstrated a significant increase in plasma KYNA concentration following cardiac surgery [ 30 ]. Likewise, Forrest et al presented an increase in plasma KYNA concentration after major surgery [ 31 ].…”
Section: Discussionsupporting
confidence: 94%
“…The kynurenine pathway has been shown to modulate tryptophan metabolism and the serotonergic system and to play critical roles in the secretion of pro-inflammatory cytokines [ 27 ]. In the kynurenine metabolic pathway, tryptophan is initially oxygenated by IDO to yield kynurenine, which is subsequently transformed by kynurenine aminotransferase to kynurenic acid [ 28 ]. Our findings showed that RSV infection markedly reduced kynurenic acid concentrations in pDCs, suggesting that RSV infection can modulate inflammatory responses in pDCs by regulating the production of kynurenic acid.…”
Section: Discussionmentioning
confidence: 99%
“…During neonatal asphyxia, the levels of KYNA rose significantly in the brain of newborn rats, whereas they fell at birth in normal newborns . In other stages, increases in plasma KYNA concentration have been reported to be correlated with inflammatory bowel disease, severe inflammation, clinical symptoms, schizophrenia and distress intolerance …”
Section: Discussionmentioning
confidence: 99%